Mewujudkan Proactive Work Behaviour dalam Implementasi Flexible Working Arrangement Pasca Pandemi Covid-19 - Eti Setyarini; Fibria Indriati (PERSPEKTIF, 2022)
This research was driven by the COVID-19 pandemic which had an impact on changes in employee working arrangements. Prior to the COVID-19 pandemic, many employees worked from the office (WFO), however, after the pandemic, many employees had the opportunity to work flexibly (either working from home or other remote work). This adaptability is part of the Flexible Working Arrangement (FWA), which is being implemented in an effort to minimize the spread of COVID-19. Various studies have found that such work arrangements, even in public organizations, will continue to be adopted after the COVID-19 pandemic. Therefore, organizations must ensure that flexible working arrangements have a positive impact on their organization. One of the efforts that can be done is to evaluate from the perspective of proactive work behaviour. In this regard, the objective of this research was to determine the best effort for implementing proactive work behaviour in the implementation of flexible working arrangements. The study was carried out with a qualitative approach and data collection techniques through documentation studies. The results indicate that proactive work behavior can be achieved in the context of implementing flexible work arrangements by: 1) establishing appropriate flexible working policies, 2) providing adequate organizational support, and 3) paying attention to employee well-being